2021
DOI: 10.1021/acs.macromol.1c01975
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between the Assembly of Individual PEDOT Chains and Their Interaction with Light

Abstract: A new method for poly (3, 4-ethylenedioxythiophene) (PEDOT) synthesis based on acid-assisted polymerization is proposed, and the optical and structural properties of the obtained material are explored. Special attention is given to the effect of the polar Bronsted acid on the formation of oligomer/polymer chains and their ability to assemble into nanoobjects. By using 1H and 13C NMR spectroscopy (in the liquid and solid state), the formation of PEDOT in a neutral state was proven. Matrix-assisted laser desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The microspheres were used as cores in the preparation of the PNaSS@PEDOT microsphere particles ( Scheme 2 ). The polymer film was obtained in the process of acid-assisted self-polymerization of the monomer (3,4-ethylenedioxythiophene, EDOT); the reaction was first described by our research group [ 44 , 45 ]. The synthesis can be summarized as follows: the prepared microspheres were dispersed in concentrated formic acid, and EDOT monomer was added to the dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The microspheres were used as cores in the preparation of the PNaSS@PEDOT microsphere particles ( Scheme 2 ). The polymer film was obtained in the process of acid-assisted self-polymerization of the monomer (3,4-ethylenedioxythiophene, EDOT); the reaction was first described by our research group [ 44 , 45 ]. The synthesis can be summarized as follows: the prepared microspheres were dispersed in concentrated formic acid, and EDOT monomer was added to the dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The acid-assisted self-polymerization of the EDOT monomer without the formation of by-products was first revealed by our research group and studied in detail [ 44 ]. The analysis of high-resolution core-level S2p X-ray photoelectron spectra (XPS) confirmed that only polymers with reduced monomer units were formed during acid-assisted self-polymerization [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations